Corrective Taxation and Internalities from Food Consumption. (20th November 2017) - Griffith, Rachel; O'Connell, Martin; Smith, Kate
Abstract: Corrective taxes have been implemented in a number of countries with the aim of addressing growing concern about the rise in obesity- and diet-related diseases. The rationale is that food consumption imposes costs on the consumer in the future that they do not fully take into account at the point of consumption ('internalities'). Corrective taxes have the potential to improve welfare by reducing suboptimally high consumption. We review the literature on the size of these internalities and on the optimal corrective tax, which depends on the patterns of internalities, the price responsiveness of consumers, and on redistributive aims. (JEL classification: H2, D9)